INFORMATION MODELS OF GENERAL NURSING CARE FOR PATIENTS WITH SUPPORT FOR DECISION ALGORITHMS BASED ON THE ICNP CLASSIFIER - Matrtseniuk, V. P.; Andrushchak, I. Ye.; Tsikorska, I. V. (Medical Informatics and Engineering, 2018)
The paper presents information models of the nursing process through a conceptual presentation, including assessments of the patient's overall condition (nursing interviews, physical assessment, measurement, documentation analysis), nursing diagnosis, nursing care planning, determination of expected results, nursing manipulation, care plan implementation and care results evaluation. Particular attention is drawn to the possibility of using international terminology in describing nursing practices. Analysis of solutions is carried out using the terminology of decision trees.